Identifying barriers to patient advocacy in the promotion of a safety culture: An integrative review - Teena Shoemark; Paula Foran (Journal of Perioperative Nursing)
Problem identification: Promoting patient safety, through patient advocacy, is an important part of the perioperative nurse role. However, identified barriers to effective patient advocacy have also reflected deficits in the characteristics of safety culture. This integrative review aims to highlight these barriers and discuss strategies for promoting patient safety within the perioperative context by presenting links between patient advocacy and safety culture.